2008
DOI: 10.1063/1.2980348
|View full text |Cite
|
Sign up to set email alerts
|

Drag and wakes of freely falling 60° cones at intermediate Reynolds numbers

Abstract: The drag coefficient for freely falling cones with a vertex angle of 60°was determined experimentally in the Reynolds number range from 90 to 8 ϫ 10 3 and described by empirical equations. The drag was determined by measurement of the terminal velocity of the cones falling through water. Flow-visualization experiments showed the different regimes of the wake structure for a wide range of the Reynolds numbers covering the successive destabilizations of the wake on the way to turbulence. Especially, a very regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…6 Visualization of the two-thread wake behind a falling thin disk (D = 7 mm, t = 55 µm) at Re = 112. Modulation of the twothread wake was observed, the Strouhal number is calculated to be 0.12 from the image close to the value 0.113 calculated by Shenoy and Kleinstreuer [12] for the fixed χ = 1/10 disk and 0.122 found in experiment of freely rising disks by Fernandes et al The oscillation of the two-thread wake was also mentioned in studies of other bodies as in sphere [4,5,7] and cone [14]. Especially, Gumowski et al [8] observed a "three dimensional peristaltic" oscillation which modulated the counter rotating vortices behind a sphere to develop at Re = 266, the shedding of hairpin-like vortices was proposed resulting from the oscillations.…”
Section: Transition Scenariomentioning
confidence: 92%
See 4 more Smart Citations
“…6 Visualization of the two-thread wake behind a falling thin disk (D = 7 mm, t = 55 µm) at Re = 112. Modulation of the twothread wake was observed, the Strouhal number is calculated to be 0.12 from the image close to the value 0.113 calculated by Shenoy and Kleinstreuer [12] for the fixed χ = 1/10 disk and 0.122 found in experiment of freely rising disks by Fernandes et al The oscillation of the two-thread wake was also mentioned in studies of other bodies as in sphere [4,5,7] and cone [14]. Especially, Gumowski et al [8] observed a "three dimensional peristaltic" oscillation which modulated the counter rotating vortices behind a sphere to develop at Re = 266, the shedding of hairpin-like vortices was proposed resulting from the oscillations.…”
Section: Transition Scenariomentioning
confidence: 92%
“…To make a comparison between various body geometries, we considered the normalized distance L/D, L was defined as the distance between the vortex cores of the two-thread wake at the same downstream location behind the bodies. The value of L/D was directly obtained from the visualization images of a disk, sphere [6] and 60 • cone [14]. However, the value of L/D depended both on the choice of downstream location and Reynolds number, so L were all measured at downstream position 4D as the two-thread wake was clearly far away from the recirculation region.…”
Section: Steady Wakementioning
confidence: 99%
See 3 more Smart Citations